Performance of the SmartMe&You serious video games for home telemonitoring is related to cognitive status and resting-state electroencephalographic markers in healthy and Parkinson’s disease participants - Claudio Del Percio; Roberta Lizio; Mina De Bartolo; Matteo Carpi; Giuseppe Noce; Susanna Lopez; Antonio Pio Afragola; Federica Fiorentino; Filippo Carducci; Veronica Henao Isaza; Paolo Barone; Arianna Cappiello; et al. (GeroScience, 2026)
Unsupervised serious video games on the SmartMe&You home telemonitoring platform may enable the assessment of cognitive fluctuations in older individuals, with or without cognitive deficits. Here, we tested their validity in cognitively unimpaired older adults (Healthy) and patients with mild cognitive impairment and mild to moderate dementia due to Parkinson’s disease (PDCD). Such validity was assessed using Mini-Mental State Examination (MMSE) scores and resting-state eyes-closed electroencephalography (rsEEG) activity. Clinical, demographic, and rsEEG datasets were collected from 34 healthy and 68 PDCD participants. The SmartMe&You video games included 7 unsupervised cognitive tasks implemented on a commercial tablet. The rsEEG source activities in the individual delta, theta, and alpha frequency bands were estimated using the eLORETA freeware. As novel findings, we showed that game performance: (1) discriminated between healthy participants and PDCD patients, with overall accuracy exceeding 90%; (2) was positively associated with MMSE scores across all participants ( p < 0.00001); and (3) was negatively associated with global rsEEG source activity in the delta and theta frequency bands ( p < 0.00001). These findings suggest that serious videogames of the SmartMe&You home telemonitoring platform were feasible and sensitive to cognitive status across the spectrum from normal aging to Parkinson’s disease-related dementia. This approach provides a scalable, low-cost, and ecologically valid tool for remote cognitive monitoring, with future potential applications in both early detection and longitudinal tracking of cognitive decline.

Associations of daily step counts with cognitive, clinical, and resting-state electroencephalographic measures in patients with cognitive decline due to Alzheimer’s disease - Matteo Carpi; Mina De Bartolo; Veronica Henao Isaza; Giuseppe Noce; Claudio Del Percio; Susanna Lopez; Filippo Carducci; Roberta Lizio; Antonio Pio Afragola; Burcu Bölükbaş; Federica Fiorentino; Angelo Barone; et al. (GeroScience, 2026)
Sedentary behavior is a recognized and modifiable risk factor for cognitive decline and dementia across neurodegenerative conditions. This study used a smartwatch-based telemonitoring procedure combined with ecological cognitive assessment to examine whether step counts can capture sedentary behavior and its association with cognitive functioning in patients with mild cognitive impairment (ADMCI) and dementia (ADD) due to Alzheimer’s disease. Then, 19 ADD, 28 ADMCI, and 23 cognitively unimpaired older adults (Nold) were consecutively recruited. Participants underwent clinical assessment, resting-state electroencephalography (rsEEG), and neuropsychological testing. They were then monitored at home for approximately one week using Samsung Galaxy Watch 4–6 devices recording step counts (total, purposeful, and incidental) and activity intensity (peak 30-min cadence), together with the unsupervised SmartMe&You-TELEMAIA serious videogame battery administered on a commercial tablet for cognitive assessment. The ADD group showed reduced step counts and lower peak cadence than both ADMCI and Nold participants, whereas rsEEG markers and cognitive measures discriminated the three groups with a graded pattern. Within the AD sample, smartwatch-derived activity metrics were associated with cognitive functioning as assessed by conventional neuropsychological testing and ecological serious videogame performance, but showed limited associations with rsEEG rhythms. EEG delta and alpha rhythms were also more abnormal in the ADD group than in the ADMCI group. Home-based daytime activity monitoring with commercial smartwatches indicated that step volume and intensity are associated with cognitive status in patients with ADMCI and ADD. These findings suggest that smartwatch-derived activity metrics may provide feasible and cost-effective markers of everyday functioning in Alzheimer’s disease. Graphical abstract a Schematic overview of the study design, including resting-state EEG, one-week smartwatch-based activity monitoring, and unsupervised ecological cognitive assessment with the SmartMe&You-TELEMAIA Platform. b Group differences in daily activity metrics across participants with Alzheimer’s disease with dementia (ADD; N = 19), Alzheimer’s disease with mild cognitive impairment (ADMCI; N = 28), and cognitively unimpaired older adults (Nold; N = 23), indicating reduced daily step volume and peak cadence mainly in ADD. c Representative significant associations within the AD clinical sample (ADD + ADMCI; up to N = 47), showing that step metrics were more closely related to cognition (MMSE) and depressive symptom severity (BDI-II) than to resting-state EEG activity, for which only limited associations emerged.

Abnormal periodic and aperiodic resting-state electroencephalographic markers in Lewy body and Alzheimer’s diseases with cognitive decline - Matteo Carpi; Antonio Pio Afragola; Mina De Bartolo; Susanna Lopez; Burcu Bölükbaş; Claudio Del Percio; Veronica Henao Isaza; Roberta Lizio; Giuseppe Noce; Lorenc Barjami; Filippo Carducci; Andrea Soricelli; et al. (GeroScience, 2026)
Lewy body disease (LBD) and Alzheimer’s disease (AD) are the most common causes of cognitive decline and dementia and are associated with characteristic alterations in resting-state electroencephalographic (rsEEG) activity. This multicenter exploratory study investigated periodic and aperiodic rsEEG features in patients with cognitive decline due to Lewy body disease (LBCD) and Alzheimer’s disease (ADCD), compared with cognitively unimpaired older adults (Nold), and examined the clinical relevance of these markers in LBCD. A total of 140 LBCD, 135 ADCD, and 118 Nold datasets from the PDWAVES archive underwent spectral parameterization to decompose rsEEG power spectra (1–30 Hz) into periodic peaks and aperiodic background activity. Both clinical groups showed a significant slowing of the individual alpha frequency (IAF), more pronounced in LBCD, along with reduced periodic alpha and beta power reflected in a lower vigilance index. The aperiodic exponent was elevated in both groups, and the aperiodic offset was also higher in LBCD, suggesting steeper spectral profiles consistent with increased inhibitory cortical tone. Within the LBCD group, poorer cognition was associated with higher low-frequency alpha power, whereas better cognition was predicted by higher high-frequency alpha power. A reduced vigilance index was associated with the presence of visual hallucinations, while no associations emerged for other symptoms. These findings suggest that combined periodic and aperiodic rsEEG features may provide relevant markers of altered vigilance regulation in LBCD. Future studies should evaluate whether these EEG markers can inform targeted interventions, such as neuromodulatory or audiovisual stimulation, to stabilize quiet-vigilance states and improve clinical outcomes. Graphical abstract Panel A shows the spectral parameterization of rsEEG activity into periodic and aperiodic components. Panel B summarizes the main group differences in key rsEEG markers across LBCD, ADCD, and Nold participants. Panel C shows the topographical associations between the vigilance index and cognition and visual hallucinations in LBCD; colors reflect the direction and strength of the associations. For the visual hallucinations map, negative log-odds indicate lower odds of hallucinations for higher vigilance index values, whereas positive log-odds indicate higher odds; values around ± 1.5 correspond approximately to odds ratios of 0.22 and 4.5, respectively. Abbreviations: rsEEG, resting-state electroencephalography; LBCD, cognitive decline due to Lewy body disease; ADCD, cognitive decline due to Alzheimer’s disease; Nold, cognitively unimpaired older adults; IAF, individual alpha frequency; MMSE, Mini-Mental State Examination; p , standardized regression coefficient; log-odds, logistic regression coefficient.

Experimental and numerical investigation of air lubrication on a planing hull with Double Interceptor System - Vincenzo Sorrentino; Riccardo Pigazzini; Fabio De Luca; Simone Mancini; Claudio Pensa (Ocean Engineering, 2025)

Water exchange rate and stocking density on the larviculture of the scallop Nodipecten nodosus in recirculation aquaculture system - Simone Sühnel; Francisco José Lagreze Squella; Francisco Carlos da Silva; Claudio Manoel Rodrigues de Melo (Aquaculture, 2024)

Stocking Density and Diet of Two Oyster (Crassostrea gasar and Crassostrea gigas) Seeds in Fluidized Bed Bottle Nursery System - Simone Sühnel; Francisco José Lagreze-Squella; Gabriel Nandi Corrêa; Jaqueline Araújo; Glauber de Souza; João Paulo Ramos Ferreira; Francisco Carlos da Silva; Carlos Henrique Araújo de Miranda Gomes; Claudio Manoel Rodrigues de Melo (Fishes, 2024)
Crassostrea is the most farmed oyster genus worldwide and has significant economic and social impacts with environmental benefits. Hatchery oyster seed production is a highly costly phase, and a fluidized nursery system can help reduce this cost and reduce seed production time. The present study evaluated the survival and growth of two oyster species (Crassostrea gasar and Crassostrea gigas) in a fluidized bed bottle nursery system. With C. gasar, two experiments were performed; one tested three stocking densities and the other three bialgae diets. With C. gigas, one experiment with a bialgae and monoalgae in an initial bottle occupation of 8.8% produced more seeds per bottle, but an initial bottle occupation of 2.2% produced bigger seeds. Also, the experiment with C. gasar and with C. gigas tested diets did not affect seed survival, but the diets with bialgae I. galbana and N. oculate promoted more seed growth. The fluidized bed bottle nursery system developed for this study was adequate for the seeds of the oysters C. gasar and C. gigas in the nursery phase.

Parent-of-origin effects for the number of oocytes and embryos in Gir cattle - Renata de Fátima Bretanha Rocha; Arielly Oliveira Garcia; Mateus Guimarães dos Santos; Pamela Itajara Otto; Marcos Vinícius Barbosa da Silva; Marta Fonseca Martins; Marco Antônio Machado; João Claudio do Carmo Panetto; Mario P.L. Calus; Jeremie Vandenplas; Simone Eliza Facioni Guimarães (Livestock Science, 2024)

High promiscuity among females of the invasive pest species Drosophila suzukii - Simone Puppato; Giulia Fiorenza; Davide Carraretto; Ludvik Marcus Gomulski; Giuliano Gasperi; Carlos Caceres; Alberto Grassi; Maria Vittoria Mancini; Antonio De Cristofaro; Claudio Ioriatti; Robin Guilhot; Anna Rodolfa Malacrida (Molecular Ecology, 2023)
Drosophila suzukii (Matsumura, 1931), the spotted‐wing drosophila, is a highly invasive fruit fly that spread from Southern Asia across most regions of Asia and, in the last 15 years, has invaded Europe and the Americas. It is an economically important pest of small fruits such as berries and stone fruits. Drosophila suzukii speciated by adapting to cooler, mountainous, and forest environments. In temperate regions, it evolved seasonal polyphenism traits which enhanced its survival during stressful winter population bottlenecks. Consequently, in these temperate regions, the populations undergo seasonal reproductive dynamics. Despite its economic importance, no data are available on the behavioural reproductive strategies of this fly. The presence of polyandry, for example, has not been determined despite the important role it might play in the reproductive dynamics of populations. We explored the presence of polyandry in an established population in Trentino, a region in northern Italy. In this area, D. suzukii overcomes the winter bottleneck and undergoes a seasonal reproductive fluctuation. We observed a high remating frequency in females during the late spring demographic explosion that led to the abundant summer population. The presence of a high degree of polyandry and shared paternity associated with the post‐winter population increase raises the question of the possible evolutionary adaptive role of this reproductive behaviour in D. suzukii .

Single-step genome-wide association studies and post-GWAS analyses for the number of oocytes and embryos in Gir cattle - Renata de Fátima Bretanha Rocha; Arielly Oliveira Garcia; Pamela Itajara Otto; Mateus Guimarães dos Santos; Marcos Vinícius Barbosa da Silva; Marta Fonseca Martins; Marco Antônio Machado; João Claudio do Carmo Panetto; Simone Eliza Facioni Guimarães (Mammalian Genome, 2023)

Runs of homozygosity and signatures of selection for number of oocytes and embryos in the Gir Indicine cattle - Renata de Fátima Bretanha Rocha; Arielly Oliveira Garcia; Pamela Itajara Otto; Marcos Vinícius Barbosa da Silva; Marta Fonseca Martins; Marco Antônio Machado; João Claudio do Carmo Panetto; Simone Eliza Facioni Guimarães (Mammalian Genome, 2023)

Late Quaternary sedimentary record of estuarine incised-valley filling and interfluve flooding: The Manfredonia paleovalley system (southern Italy) - Alessandro Amorosi; Luigi Bruno; Massimo Caldara; Bruno Campo; Simone Cau; Vincenzo De Santis; Andrea Di Martino; Wan Hong; Giorgio Lucci; Claudio Pellegrini; Veronica Rossi; Irene Sammartino; et al. (Marine and Petroleum Geology, 2023)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluating mortality rates with a novel integrated framework for nonmonogamous species - Simone Tenan; Aaron Iemma; Natalia Bragalanti; Paolo Pedrini; Marta De Barba; Ettore Randi; Claudio Groff; Meritxell Genovart (Conservation Biology, 2016)
The conservation of wildlife requires management based on quantitative evidence, and especially for large carnivores, unraveling cause‐specific mortalities and understanding their impact on population dynamics is crucial. Acquiring this knowledge is challenging because it is difficult to obtain robust long‐term data sets on endangered populations and, usually, data are collected through diverse sampling strategies. Integrated population models (IPMs) offer a way to integrate data generated through different processes. However, IPMs are female‐based models that cannot account for mate availability, and this feature limits their applicability to monogamous species only. We extended classical IPMs to a two‐sex framework that allows investigation of population dynamics and quantification of cause‐specific mortality rates in nonmonogamous species. We illustrated our approach by simultaneously modeling different types of data from a reintroduced, unhunted brown bear ( Ursus arctos ) population living in an area with a dense human population. In a population mainly driven by adult survival, we estimated that on average 11% of cubs and 61% of adults died from human‐related causes. Although the population is currently not at risk, adult survival and thus population dynamics are driven by anthropogenic mortality. Given the recent increase of human‐bear conflicts in the area, removal of individuals for management purposes and through poaching may increase, reversing the positive population growth rate. Our approach can be generalized to other species affected by cause‐specific mortality and will be useful to inform conservation decisions for other nonmonogamous species, such as most large carnivores, for which data are scarce and diverse and thus data integration is highly desirable.

Impact of explosive volcanic eruptions around Vesuvius: a story of resilience in Roman time - Claudio Scarpati; Annamaria Perrotta; Girolamo Ferdinando De Simone (Bulletin of Volcanology, 2016)

A statistical approach to evaluate compost genotoxicity - Claudio De Simone; Rita Angelucci; Manuela Francesca Errichetti; Simona Marconi; Marcello Rossi; Sabrina Selvi (Biology and Fertility of Soils, 2005)